The Effect of Role Stress on Auditor Burnout (Empirical Study on the Denpasar City Inspectorate) - I Gst Ayu Agung Pramesti Pramana Putri; Ni Putu Sri Harta Mimba; Luh Gede Krisna Dewi (Universitas Dwijendra Press, 2026)
The Denpasar City Inspectorate faces an imbalance in human resources with a ratio of 31 employees out of an ideal need of 104 people, potentially causing role stress that contributes to auditor burnout. This study analyzes the influence of role stress which includes role conflicts, role ambiguity, and role overload on burnout auditors at the Denpasar City Inspectorate. The research methodology uses an explanatory quantitative approach with a census method involving 31 internal auditor respondents. The questionnaire instrument used a Likert scale that was analyzed through multiple regression after meeting tests of validity, reliability, and classical assumptions. The results of the regression analysis showed an adjusted R² of 0.838, indicating that 83.8% of the burnout auditor variance was explained by role stress. Role conflicts demonstrated the dominant influence with a coefficient of 1.895 and significance of 0.000, followed by role ambiguity with a coefficient of 0.576 and significance of 0.009, and overload of roles with a coefficient of 0.517 and significance of 0.009. The conclusion of the study confirms that the three dimensions of role stress have a positive and significant effect on auditor burnout, with role conflict as the strongest predictor in this research model, thus confirming the urgency of implementing optimal human resource management to minimize the level of burnout and increase the effectiveness of the implementation of internal audits of local governments.